The Effect of Entrepreneurial Knowledge on Entrepreneurial Intention with the Moderation of Family Support (A Case Study on University Students in Indonesia) - Ikhram, Abdi Dzil; Novadjaja, Lily Hendrasti (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
Unemployment still becomes a major problem for most developing countries like Indonesians. It is generally acknowledged that one of the efforts to overcome such problem is by creating new employments, particularly entrepreneurship and in this respect to enhanced through entrepreneur education. Should it be given college students, it will provide prominent influence in the development of entrepreneurship activities., in addition, several studies also mention that family support is also influential, where children of entrepreneurs or people who own businesses tend to be entrepreneurs. Both factors are expected to raise student’s entrepreneurial intention, people’s intention to start ventures. This study intends to identify the effect of entrepreneurial education and family support on entrepreneurial intention. This study uses a survey method with questionnaires and Partial Least Squares as its statistical instrument surveying all university students in Malang Raya who have taken entrepreneurship course. Both hypotheses of this study are accepted were the main result stating that entrepreneurial knowledge positively and significantly influences entrepreneurial intention. Others major implications are also discussed in this article.